Delta Making Community Engagement in Padang Panjang Work Training Center - Yuliarni Yuliarni1; Widdiyanti Widdiyanti; Maulid Hariri Gani; Yandri Yandri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
In Minangkabau society, deta can serve as both a social status indicator and the identity of a society. The government makes an effort to introduce and maintain the local cultures. One of them is having pupils in elementary school through secondary school wear regionally specific traditional clothing as their school uniform. The public now has more opportunities to participate in the creative economy because to this legislation. The Padang Panjang Vocational Training Center (BLK) trains residents of Padang Panjang to work as data suppliers for students in West Sumatra as well as Padang Panjang. In addition to lectures and Q&A sessions, this activity also involves direct practice or demonstrations. Sewing and written batik are the techniques that are taught. Students are able to create deta as a result of this training activity, from processing fabric through producing deta that is suitable for use.